THE ROLE OF BRAND IMAGE IN MEDIATED AMENITIES IN INCREASING TOURIST SATISFACTION - Pantun Harianja; Fuji Rahmadi; Rusiadi Rusiadi; Ade Novalina; Bhaktiar Efendi; Lia Nazliaan Nasution; Suhendi Suhendi; Diwayana Putri Nasution (Proceeding of The International Conference on Economics and Business, 2022)
Destination study that is for the role of brand image in mediate amenity to satisfaction tourists in Bukit Lawang . Method analysis by year first in study this use approach SEM (Structural Equation Modelling) . Research results show that 1) By straight a minute have influence positive and significant to brand image on Bukit Lawang . 2) In straight a minute have influence positive and significant to tourist satisfaction at Bukit Lawang . 3) In no direct brand image has role significant in mediate a minute to tourist satisfaction at Bukit Lawang .